USE OF DIFFERENT TANNIN-BASED COAGULANTS FOR TREATMENT OF SURFACE WATER WITH HIGH SUSPENSION SOLIDS LOAD (REMUNOM, 2024)
Water is one of the essential natural resources for life on Earth and especially for human consumption. However, in order to become drinkable, it often needs to undergo physical and chemical processes for consumption. One of these processes is the coagulation stage, which is a fundamental method in treatment, where solids are separated from the water by decantation using a coagulating agent, which is most often an inorganic salt such as aluminum or iron sulfate, which can seriously affect the environment if the waste is disposed of incorrectly. This study aimed to evaluate the potential performance of tannin-based coagulants in the treatment of waters from the middle Amazon. The following physical and chemical parameters were evaluated: pH, color, turbidity, electrical conductivity, temperature and total suspended solids. Solutions of 1% of the coagulants Tanfloc SG®️, MTH®️ and MT®️ were prepared, treated with predetermined volumes of 8, 10, 12, 14 and 20 mL. The results showed little variation in pH even after treatment with a value between 6-8, being good for consumption, a situation that avoids the use of chemical products for correction. The best in efficiency, mainly in removing turbidity and maintaining pH were Tanfloc SG®️ (8.0 mL), Tanfloc MTH®️ (14.0 mL) and Tanfloc MT®️ (12.0 mL) with a removal percentage higher than 95%. Regarding the sedimentation time, they took around 35 minutes for their deposition. Therefore, the natural coagulants from biomolecules such as tannins that were analyzed have the potential to replace inorganic coagulants and facilitate the disposal of the final residue.Keywords: Natural coagulant; Tanfloc; water treatment; physical-chemical variables.